Studying Japan: Handbook of Research Designs, Fieldwork and Methods - Kottmann, Nora; Reiher, Cornelia (Nomos Verlagsgesellschaft mbH & Co. KG, 2020)
Studying Japan is the first comprehensive guide on qualitative methods, research designs and fieldwork in social science research on Japan. More than 70 Japan scholars from around the world provide an easy-to-read overview on qualitative methods used in research on Japan’s society, politics, culture and history. The book covers the entire research process from the outset to the completion of a thesis, a paper, or a book. The authors provide basic introductions to individual methods, discuss their experiences when applying these methods and highlight current trends in research on Japan. The book serves as a foundation for a course on qualitative research methods and is, but can also be used as a reference for all researchers in Japanese Studies, the Social Sciences and Area Studies. It is an essential reading for students and researchers with an interest in Japan!With contributions by: Chapter: Celeste L. Arrington, David Chiavacci, Andreas Eder-Ramsauer, James Farrer, Roger Goodman, Carola Hommerich, Nora Kottmann, Gracia Liu-Farrer, Levi McLaughlin, Chris McMorran, Caitlin Meagher, Kaori Okano, Theresia B. Peucker, Cornelia Reiher, Katja Schmidtpott, Christian Tagsold, Katrin Ullmann, Gabriele Vogt, Cosima Wagner, Akiko Yoshida and Urs Matthias Zachmann.Essays: Shinichi Aizawa, Noor Albazerbashi, Daniel P. Aldrich, Allison Alexy, Verena Blechinger-Talcott, Christoph Brumann, Genaro Castro-Vázquez, David Chiavacci, Jamie Coates, Emma E. Cook, Laura Dales, James Farrer, Flavia Fulco, Isaac Gagné, Nana Okura Gagné, Sonja Ganseforth, Sheldon Garon, Julia Gerster, Christopher Gerteis, Markus Heckel, Steffen Heinrich, Joy Hendry, Swee-Lin Ho, Barbara Holthus, Katharina Hülsmann, Jun Imai, Hanno Jentzsch, Aya H. Kimura, Emi Kinoshita, Susanne Klien, Gracia Liu-Farrer, Patricia L. Maclachlan, Wolfram Manzenreiter, Kenneth M. McElwain, Lynne Y. Nakano, Scott North, Robin O’Day, Robert J. Pekkanen, Saadia M. Pekkanen, Isabelle Prochaska-Meyer, Nancy Rosenberger, Richard J. Samuels, Annette Schad-Seifert, Katja Schmidtpott, Tino Schölz, Kai Schulze, Kay Shimizu, Karen Shire, David H. Slater, Celia Spoden, Brigitte Steger, Nicolas Sternsdorff-Cisterna, Christian Tagsold, Akiko Takeyama, Daisuke Watanabe, Daniel White, Anna Wiemann and Tomiko Yamaguchi.Foreword: Ilse Lenz and Franz Waldenberger.